Anticonvulsant Activity of Essential Oil From Leaves of Zhumeria majdae (Rech.) in Mice: The Role of GABAA Neurotransmission and the Nitric Oxide Pathway - Helia Aghamiri; Hamed Shafaroodi; Jinous Asgarpanah (Wiley, 2020)
The essential oil from the leaves of Zhumeria majdae Rech. (ZMEO) has been shown to have several beneficial effects in the clinic. In this work we examined the anticonvulsant activities of ZMEO in an experimental mouse model of seizure and aimed to identify any possible underlying mechanisms. ZMEO (5, 10, 20, and 40 mg/kg intraperitoneally (i.p.)) or diazepam, as the reference anticonvulsant drug (25, 50 and 100 µg/kg i.p.), were administered 60 minutes prior to pentylenetetrazol (PTZ) injection (intravenously (i.v.) or i.p.) and changes in threshold, latency, and frequency of clonic seizure were examined. The PTZ i.p.‐induced model of seizure was also applied for examining the protective effects of ZMEO pretreatment against PTZ‐induced mortality. In some studies, the anticonvulsant effect of the combination of diazepam and ZMEO was also studied. The protective effects of ZMEO against hindlimb tonic extensions (HLTEs) were also examined by maximal electroshock (MES) seizure testing. The γ‐aminobutyric acid (GABA)ergic mechanism and nitric oxide (NO) pathway involvement in anticonvulsant activity of ZMEO were assessed by pretreating animals with flumazenil, Nω‐nitro‐L‐arginine methyl ester (L‐NAME), aminoguanidine, and L‐arginine in a PTZ‐induced model of seizure. Administration of 20 mg/kg ZMEO significantly increased chronic seizure threshold and latency while reducing frequency of convulsions and mortality in the PTZ‐induced model. In the doses studied, ZMEO could not protect mice from HLTE and mortality induced by MES. Pretreatment with L‐arginine and diazepam potentiated the anticonvulsant effects of ZMEO, whereas pretreatment with L‐NAME, aminoguanidine, and flumazenil reversed anticonvulsant activity. The anticonvulsant activity of ZMEO may be mediated in part through a GABAergic mechanism and the NO signaling pathway.